2020
DOI: 10.1164/rccm.202003-0524le
|View full text |Cite
|
Sign up to set email alerts
|

Time Kinetics of Viral Clearance and Resolution of Symptoms in Novel Coronavirus Infection

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; previously called "2019-nCoV"; the virus that causes coronavirus disease [COVID-19]) has infected .1,773,000 patients and killed .111,650 people worldwide as of April 13, 2020 (1). It has been reported that a patient in Germany had high viral titers after the resolution of fever and infected two close contacts after the resolution of symptoms (2). In the wake of these cases, it is still unclear how long the patient was virus positive after the resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
3
10

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(167 citation statements)
references
References 9 publications
8
146
3
10
Order By: Relevance
“…Among 16 patients with predominantly mild disease, they found that the median duration of symptoms was 8 days. They found that 8 patients remained real-time PCR positive beyond symptom resolution for a median of 2.5 days after clinical recovery (1). These findings are in congruence with the work of Young et al who reported that SARS-CoV-2 remained detectable by PCR in nasopharyngeal swabs for a median duration of 12.5 days after symptom onset.…”
Section: To the Editorssupporting
confidence: 78%
“…Among 16 patients with predominantly mild disease, they found that the median duration of symptoms was 8 days. They found that 8 patients remained real-time PCR positive beyond symptom resolution for a median of 2.5 days after clinical recovery (1). These findings are in congruence with the work of Young et al who reported that SARS-CoV-2 remained detectable by PCR in nasopharyngeal swabs for a median duration of 12.5 days after symptom onset.…”
Section: To the Editorssupporting
confidence: 78%
“…27 If patients develop symptoms subsequent to a positive test, then a longer delay before bronchoscopy is needed. 28,29 Critically, we note that sensitivity of nasopharyngeal swab for COVID-19 infection has been reported at 71-83% among symptomatic patients, 30,31 and may be even lower among asymptomatic patients. Given the numerous reports regarding false-negative results for nasopharyngeal swab reverse transcriptase (RT)-PCR testing, 32,33 we recommend universal precautions, including PPE (below), be applied even in the event of a negative nasopharyngeal swab result.…”
Section: Pre-procedures Screeningmentioning
confidence: 72%
“…Current estimates are that viral shedding can occur for up to 2 weeks or more after improvement of symptoms, but there is also considerable variation (maximum observed shedding of 37 days). [7][8][9] There is also an association between severity of illness and peak viral loads, which may in turn influence the duration of subsequent viral shedding. 10 Thus, given the present uncertainty, our current clinical practice has been to delay reintroduction of these agents for up to 2 weeks after discharge, recognizing that prolonged reduction of immunosuppression increases the risk of allograft rejection.…”
Section: Discussionmentioning
confidence: 99%